Minimum-time trajectories during the curve in long track speed skating - Takenaka, S.; Fujii, N.; Suzuki, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Athletes skate an oval track in a short period of time as much as possible. However, if skater try to shorten the distance in curve phase, the larger centripetal force is required. Trajectory optimization for a car driving has been presented (Velenis, E. et al., 2005), but it is not clear for speed skating. The aim of this study was to determine minimum-time trajectories during the inner curve in long-track speed skating. Method: We determined averaged patterns of force during curve stroke from displacement of body center of mass that was analyzed at the official 5000-m race (World single distances championship 2008, Nagano, Japan). In this study, we set one-mass model with eleven variables; point of entry, approach angle, changing rates of pitch and force. The object function was set as a split time of curve phase. These variables were optimized by use genetic algorithm. Initial speed in this model was 12.5m/s. Air frictional force was estimated by use in the previous study (de Koning et al. 1999). Results and Discussions: The point of entry to curve phase was inside of the course center, and Approach angle was small. Changing rates of force during stroke was increased over the curve phase, and skating speed was also increased. The innermost point of the course in trajectories was near half of the curve phase. These results were similar to measured values. We concluded that Elite athletes already take the optimal line to minimize time at curve phase in accordance with the initial speed.